Seasonal distribution and abundance of cetaceans within French waters- Part I: The North-Western Mediterranean, including the Pelagos sanctuary - Laran, Sophie; Pettex, Emeline; Authier, Matthieu; Blanck, Aurélie; David, Lea; Dorémus, Ghislain; Falchetto, Hélène; Monestiez, Pascal, P.; van Canneyt, Olivier; Ridoux, Vincent (Deep Sea Research Part II: Topical Studies in Oceanography, 2017)
International audience The biodiversity of the Mediterranean Sea is undergoing important changes. Cetaceans, as top predators, are animportant component of marine ecosystems. The seasonal distribution and abundance of several cetaceanspecies were studied with a large aerial survey over the North-Western Mediterranean Sea, including theinternational Pelagos sanctuary, the largest Marine Protected Area (MPA) designed for marine mammals in theMediterranean. A total of 8 distinct species of cetaceans were identified, and their occurrence within thesanctuary was investigated. Abundance estimates were obtained for three groups of species: the smalldelphinids (striped dolphins mainly), the bottlenose dolphin and the fin whale. There was a seasonal variationin striped dolphin abundance between winter (57,300 individuals, 95% CI: 34,500–102,000) and summer(130,000, 95% CI: 76,800–222,100). In contrast, bottlenose dolphin winter abundance was thrice that ofsummer. It was also the only species to exhibit any preference for the Pelagos sanctuary. Fin whale abundancehad the reverse pattern with winter abundance (1000 individuals, 95% CI: 500–2500) and summer (2500individuals, 95% CI: 1500–4300), without any preference for the sanctuary. Risso's dolphins, pilot whales andsperm whales did not exhibit strong seasonal pattern in their abundance. These results provide baselineestimates which can be used to inform conservation policies and instruments such as the Habitats Directive orthe recent European Marine Strategy Framework Directive.